We'll expand the binomial and we'll
get:
(1+x)^6 = a0 + a1*x + a2*x^2 + ... +
a6*x^6
a0,a1,a2,...,a6 are the coefficients of
polynomial.
The sum of even coefficients
is:
a0 + a2 + a4 + a6
We know
that if we want to determine the summof all coefficients of a polynomial, we'll have to
make the variable x = 1.
We'll put x = 1 and we'll
calculate:
(1 + 1)^6 = a0 + a1*1 + a2*1^2 + ... +
a6*1^6
a0 +a1 + ... + a6 = 2^6
(1)
Now, we'll put x = -1
(1 -
1)^6 = a0 -a1 + ... - a5 + a6
a0 -a1 + ... - a5 + a6 = 0
(2)
We'll add (1) + (2):
a0
+a1 + ... + a6 + a0 -a1 + ... - a5 + a6 = 2^6
We'll
eliminate and combine like terms:
2(a0 + a2 + a4 + a6) =
2^6
a0 + a2 + a4 + a6 =
2^6/2
a0 + a2 + a4 + a6 =
2^5
The sum of even coefficientas of the
given polynomial is: a0 + a2 + a4 + a6 = 2^5
No comments:
Post a Comment